Meniere’s disease: an inner ear disease caused by multiple factors - Huaili JIANG; Xinsheng HUANG (Zhongguo Linchuang Yixue)
Meniere’s disease (MD) is an inner ear disorder characterized by recurrent vertigo, fluctuating hearing loss, tinnitus, and aural fullness. The pathogenesis of MD remains unclear but is closely associated with endolymphatic hydrops (EH), immune dysregulation, genetic predisposition, vascular dysfunction, and viral infection. This review summarizes recent research advances of MD pathogenesis, suggesting that MD may be a heterogeneous condition with distinct subtypes driven by different mechanisms. Future studies should integrate multi-omics analyses and animal models to elucidate its molecular pathways.